Integration of Telecom Databases with Geodatabase Model for The Effective Telecom Network Management Through Geo-Informatics - Abid Hussain; Jamil Hasan Kazmi; Mudassar Hassan Arsalan (Journal of Basic & Applied Sciences, 2017)
A significant technological advancement and enhanced telecom networks, immensely evolving telecom industry around the globe. Very tough competition, financial and inventory controls have necessitated telecom companies to maximum utilization of installed telecom network and provide high quality of uninterrupted service to the customers. In this paper we describe the integrated geodatabase model offering solution to the problem of telecom operations, network infrastructure management, optimized network planning, and business operation in telecom sector. It is based on integration of telecom operations, business, parcel base data and base map of Misri Shahtelephone exchange service area. Telecom data usually maintained by different | department in scattered form consequently many operational and business related activities especially network planning and management requires optimized platform to handle all telecom issues systematically. GIS is widely recommended to meet the requirements of telecom industry. A well designed rigorous GIS data models not only supports standard GIS functions but also supports to model telecom network up to port level competently. These models instantiated on the map provide a geographical representation of the physical telecom network and those supports several operational and business functions right from customer contact, service order, network planning, engineering and many other functional areas. This paper will examine various techniques and methodologies for model telecommunication network and integration of databases for the effective management of telecom network infrastructure with spatial context of operational and business perspectives.